Speech Acts Analysis on a Companion of Child Victim of Sexual Violence Crimes in an Investigative Interview - Dhion Meitreya Vidhiasi (Universitas Sanata Dharma, 2025)
This research is a forensic linguistic study that concentrates on the analysis of speech acts spoken by a companion from one of the representative offices of a ministry in Cilacap during an investigative interview between an investigator and a child victim of a sexual violence crime. The purpose of this investigation is to examine the speech of a child victim and a companion during an investigative interview that occurred at a police station in Cilacap. This investigation is qualitative in nature and is structured as a case study. Speech data were collected during the investigative interview using listening and note-taking techniques. The data were subsequently analyzed in accordance with Weigand’s (2010) dialogic speech act theory. Additionally, the function and authority of a companion in the investigative interview process are clarified by the Regulation of the Minister of Women Empowerment and Child Protection of the Republic of Indonesia (Permen PPPA) No. 2 of 2022. The analysis results indicate that the code of ethics outlined in Permen PPPA No. 2 of 2022 is contravened by the companion’s dominance of the explorative speech act and the presence of the directive speech act. This implies that the companion must be re-informed about the code of ethics outlined in the Women Empowerment and Child Protection Regulation No. 2 of 2022. The findings of this research have the potential to assist the relevant ministries in enhancing the efficacy and authority of an assistant in the interview process related to the investigation of sexual violence crimes.